Distributed content-based visual information retrieval system on peer-to-peer networks. - King, Irwin; Ng, Cheuk Hang.; Sia, Ka Cheung
With the recent advances of distributed computing, the limitation of information retrieval from a centralized image collection can be removed by allowing distributed image data sources to interact with each other for data storage sharing and information retrieval. In this article, we present our design and implementation of DISCOVIR: DIStributed COntent-based Visual Information Retrieval system using the Peer-to-Peer (P2P) Network. We describe the system architecture and detail the interactions among various system modules. Specifically, we propose a Firework Query Model for distributed information retrieval, which aims to reduce the network traffic of query passing in the network. We carry out experiments to show the distributed image retrieval system and the Firework information retrieval algorithm. The results show that the algorithm reduces network traffic while increases searching performance.
Keywords: Peer to peer (P2) network; Content based image retrieval (CBIR).; Information retrieval; Intelligent query routing; Peer clustering